1975
DOI: 10.1136/ard.34.6.506
|View full text |Cite
|
Sign up to set email alerts
|

Potassium metabolism in patients with rheumatoid arthritis. Effects of treatment with depot tetracosactrin, spironolactone, and oral supplements of potassium chloride.

Abstract: . Potassium metabolism in patients with rheumatoid arthritis. Effects of treatment with depot tetracosactrin, spironolactone, and oral supplements of potassium chloride. (1) Plasma and urine electrolytes and whole body potassium have been measured before and after a 2-week administration of depot tetracosactrin 0 5 mg on alternate days to eight patients with rheumatoid arthritis (RA). The effects of adding supplements of potassium chloride (48 mmol/d) and spironolactone 200 mg daily have been investigated. (2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

1978
1978
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…A significant correlation was obtained between the total serum potassium and total body potassium and also between the total erythrocyte potassium and total body potassium. These latter findings confirm those of Boddy et al (1976) and in view of the anomalies noted in a study of potassium in patients with rheumatoid arthritis (Nuki et al, 1975) this method would seem to provide a simple basis for assessing further the status of potassium in this and possibly other disease situations.…”
Section: Discussionsupporting
confidence: 89%
“…A significant correlation was obtained between the total serum potassium and total body potassium and also between the total erythrocyte potassium and total body potassium. These latter findings confirm those of Boddy et al (1976) and in view of the anomalies noted in a study of potassium in patients with rheumatoid arthritis (Nuki et al, 1975) this method would seem to provide a simple basis for assessing further the status of potassium in this and possibly other disease situations.…”
Section: Discussionsupporting
confidence: 89%
“…T cells isolated from the synovial fluid of patients with RA were characterized as mainly Kv1.3 high CCR7 [21]. Experimental evidence supports the inhibitory effects of serum K on free radical formation and-oxidant damage [74]. However, the relationship between dietary K and K ion channels has not been investigated.…”
Section: Potassium (K)mentioning
confidence: 99%
“…Weber (1974) advocated a strong link between potassium and RA (15,32). NHANES population surveys in USA reported a relatively low serum potassium in RA patients and an inadequate intake of potassium (16,33). A study from UK reported a low body potassium status (17).…”
Section: Discussionmentioning
confidence: 99%
“…Potassium is an essential micronutrient in health and disease ( 12,13). There are few published reports to suggest a clinical and a therapeutic role for potassium in RA but the evidence so far seems meager (14,15,16,17,18). The current study was planned against this background.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation